A Case Series of Gestational Choriocarcinoma with Review of Literature - Anusha Tanneru; Vijith Shetty; Neetha Nandan (Indian Journal of Medical and Paediatric Oncology)
Choriocarcinoma can be gestational and nongestational. Gestational choriocarcinoma is rare with an incidence of 9.2 in 40,000 pregnancies in Asian population. They can occur following molar, partial molar pregnancy, abortion, or delivery. It is detected by elevated levels of serum beta-human chorionic gonadotropin (beta-hCG) and by imaging modality. The need for histopathological diagnosis for choriocarcinoma is debatable. Six cases of choriocarcinoma are described with variable presentations and outcomes. Out of six cases, three were following vaginal delivery, two were after abortion, and one case was perimenopausal with antecedent pregnancy 10 years ago, unclear whether it was the cause for choriocarcinoma. Brain and lung metastasis were seen in three cases each; one case, which had metastasis to all organs, had worse prognosis and succumbed to the disease. All belonged to high-risk group according to International Federation of Gynaecology and Obstetrics score (8–13). The prognosis is usually very good, provided that prompt diagnosis and treatment are initiated early. Long-term follow-up with beta-hCG levels needs to be done to detect recurrence but it did not act like a prognostic indicator in our case series.